STUDI PENGEMBANGAN WISATA BAHARI UNTUK MENINGKATKAN KUNJUNGAN WISATAWAN DI PANTAI NATSEPA KOTA AMBON PROVINSI MALUKU - Ferdinandus, Alfriani Maria; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 2 No 2 (2014): VOL 2, NO 2 (2014): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT Natsepa beach is one of the famous tourist attraction in the city of Ambon Maluku province, which is located in the Central Coast city is a strategic coastal beauty and has the potential to serve as a marine tourism activities. purpose of this study was to determine the tourism potential is Natsepa Beach, as well as to know what marine tourism activities suitable for Natsepa Beach. Research methodology is a qualitative descriptive method, by looking at the strengths, weaknesses, opportunities, and threats, as well as known results, namely the potential of natural beauty, and accessibility are more dominant.
Keywords: Tourism Development, Potential Tourism, Marine Tourism